2020
DOI: 10.1007/s11548-020-02195-y
|View full text |Cite
|
Sign up to set email alerts
|

Light source calibration for multispectral imaging in surgery

Abstract: Purpose Live intra-operative functional imaging has multiple potential clinical applications, such as localization of ischemia, assessment of organ transplantation success and perfusion monitoring. Recent research has shown that live monitoring of functional tissue properties, such as tissue oxygenation and blood volume fraction, is possible using multispectral imaging in laparoscopic surgery. While the illuminant spectrum is typically kept constant in laparoscopic surgery and can thus be estimated from preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Details on the framework can be found on https://github.com/wiesenfa/challengeR . We have observed that the toolkit has already been used by several users for challenge evaluation 28 , 29 and algorithm validation 30 in general. Other authors have adopted concepts from the toolkit, such as bootstrapping for investigating ranking variability 31 .…”
Section: Open-source Challenge Visualization Toolkitmentioning
confidence: 99%
“…Details on the framework can be found on https://github.com/wiesenfa/challengeR . We have observed that the toolkit has already been used by several users for challenge evaluation 28 , 29 and algorithm validation 30 in general. Other authors have adopted concepts from the toolkit, such as bootstrapping for investigating ranking variability 31 .…”
Section: Open-source Challenge Visualization Toolkitmentioning
confidence: 99%
“…Some team members commented that having to dim the lights to acquire HSI was a little limiting. Further work to provide on-the-fly image calibration crucial to acquire interpretable and quantitative HSI data that can deal with changing light conditions in the OR during surgical procedures such as recently proposed in Ayala et al ( 2020 ) is therefore in progress. Additionally, we intend to conduct further in-patient intraoperative studies with a larger number of patients to fully assess and appraise the use of our iHSI device during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption of separability is intuitive from the discussion of vignetting and color constancy being addressed separately in the literature 16 , 18 , 19 , 25 , 26 . By convention, to achieve a well-posed decomposition, we constrain it such that maxi,j V(i,j)=1 and 1NnS(n)=1.…”
Section: Methodsmentioning
confidence: 99%
“…Spectral and spatial vignetting corrections can also be performed independently. Reference 16 proposed to use specular highlight analysis for spectral correction. This requires additional low exposure images to be obtained to prevent saturation in the specular reflection regions.…”
Section: Introductionmentioning
confidence: 99%